Efficiency Of Water Use In Irrigation In The Northern Al- Kabeer River Basin - سليمان محمد; نضال درويش; سوسن هيفا; حيان سليمان (Latakia University Journal -Biological Sciences Series, 2025)
The study was conducted in the Northern Al- Kabeer River Basin with the aim of scientific diagnosing the problems of water resources in the river basin, which contributes to improving the management of these resources and planning agricultural production. A statistical analysis of the water resource and the quantities of water stored in the 16 Tishreen Dam was carried out to identify its general trend. The results showed that there is a surplus of water in the river basin, but there are many problems, including the weakness of water culture and awareness among farmers, and the weak material and logistical capabilities in the management of water resources in the governorate. The regression line of stored water volumes has predicted a gradual decrease over time, demonstrating that the region is vulnerable to climate change. The results of the water analysis showed the presence of fecal bacilli contamination. The study stressed the need to re-plan future agricultural cycles on the basis of crops with relatively lower water rationing and higher economic returns, and to expand the use of drip irrigation, especially in citrus orchards, as there is a possibility of developing new areas for irrigation by modern methods estimated at 15,952 hectares.